2016
DOI: 10.3325/cmj.2016.57.425
|View full text |Cite
|
Sign up to set email alerts
|

Development and the initial validation of a new self-administered questionnaire for an early detection of health status changes in smokers at risk for chronic obstructive pulmonary disease (MARKO questionnaire)

Abstract: AimTo develop and do an initial validation of a new simple tool (self-administered questionnaire) that would be sensitive and specific enough to detect early changes in smokers leading to future development of chronic obstructive pulmonary disease (COPD).Methods224 consecutive participants (50.9% women), with mean ± standard deviation age of 52.3 ± 6.7 years, 37.5 ± 16.7 pack-years smoking history (85.8% active smokers), and no prior diagnosis of COPD were recruited. The MARKO questionnaire was self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Phase I of the MARKO study will be used to test the psychometric characteristics of the MARKO questionnaire; to evaluate discriminative power of the MARKO questionnaire together with COPD-6™ measurements between different developmental stages of COPD; to identify diagnostic parameters that are most sensitive for early impairment in COPD (discriminate between COPD GOLD 0 and 1); to compare the MARKO questionnaire with other measures used to evaluate patients (HRQoL, history, physical, lung function, functional capacity); and to assess the prevalence of different stages of COPD (specifically GOLD 0 and 1) in the population at risk for COPD. Preliminary data from Phase I of initial validation of the MARKO questionnaire showed the potential for the MARKO questionnaire to assess early health status changes in smokers at risk for chronic obstructive pulmonary disease [ 31 ]. Although exclusion criteria were introduced to exclude subjects with acute/subacute clinical disorders or states of recovery from major clinical disorders representing an absolute or relative contraindication for spirometry or significantly influencing the diagnostic process, the data analysis showed that more than half (56.3%) of the recruited subjects had one or more (up to 3) comorbidities (28.6% hypertension, 10% dyslipidemia, 5.2% diabetes and 4.9% peptic syndrome, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase I of the MARKO study will be used to test the psychometric characteristics of the MARKO questionnaire; to evaluate discriminative power of the MARKO questionnaire together with COPD-6™ measurements between different developmental stages of COPD; to identify diagnostic parameters that are most sensitive for early impairment in COPD (discriminate between COPD GOLD 0 and 1); to compare the MARKO questionnaire with other measures used to evaluate patients (HRQoL, history, physical, lung function, functional capacity); and to assess the prevalence of different stages of COPD (specifically GOLD 0 and 1) in the population at risk for COPD. Preliminary data from Phase I of initial validation of the MARKO questionnaire showed the potential for the MARKO questionnaire to assess early health status changes in smokers at risk for chronic obstructive pulmonary disease [ 31 ]. Although exclusion criteria were introduced to exclude subjects with acute/subacute clinical disorders or states of recovery from major clinical disorders representing an absolute or relative contraindication for spirometry or significantly influencing the diagnostic process, the data analysis showed that more than half (56.3%) of the recruited subjects had one or more (up to 3) comorbidities (28.6% hypertension, 10% dyslipidemia, 5.2% diabetes and 4.9% peptic syndrome, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Although exclusion criteria were introduced to exclude subjects with acute/subacute clinical disorders or states of recovery from major clinical disorders representing an absolute or relative contraindication for spirometry or significantly influencing the diagnostic process, the data analysis showed that more than half (56.3%) of the recruited subjects had one or more (up to 3) comorbidities (28.6% hypertension, 10% dyslipidemia, 5.2% diabetes and 4.9% peptic syndrome, etc.) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MARKO questionnaire is a newly constructed HRQoL questionnaire developed by a group of experts. The questionnaire and the psychometric characteristics were already published elsewhere ( Vrbica et al, 2016 ). The questionnaire comprises 18 questions covering the manifestation and frequency of the symptoms already present at early stages of COPD ( Supplemental Material ).…”
Section: Methodsmentioning
confidence: 99%